2014
DOI: 10.1055/s-0034-1365543
|View full text |Cite
|
Sign up to set email alerts
|

Urgent double balloon endoscopy provides higher yields than non-urgent double balloon endoscopy in overt obscure gastrointestinal bleeding

Abstract: Background and study aims: In overt obscure gastrointestinal bleeding (OV), double balloon endoscopy (DBE) is recommended as one of the most important investigations as it can provide both diagnosis and treatment. However, there is no set standard on the timing of DBE in OV. The aim of this study was to compare the diagnostic and therapeutic yields between urgent and non-urgent DBE in patients with OV. Patients and methods: Between January 2006 and February 2013, 120 patients with OV who underwent DBE were ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 20 publications
4
43
0
Order By: Relevance
“…A recent study reported a high diagnostic and therapeutic yield (90%) with early (within 24 hours) DBE 83 in 10 patients with overt small-bowel bleeding. Another retrospective study 84 showed a higher diagnostic yield and lower incidence of recurrent bleeding with urgent DBE (within 72 hours after the last visible GI bleeding) compared with non-urgent DBE (diagnostic yield of 70% vs 30%; P < .05) in 120 patients with obscure smallbowel bleeding. These studies suggest that early intervention with DBE may yield better outcomes.…”
Section: Role Of Vcementioning
confidence: 97%
“…A recent study reported a high diagnostic and therapeutic yield (90%) with early (within 24 hours) DBE 83 in 10 patients with overt small-bowel bleeding. Another retrospective study 84 showed a higher diagnostic yield and lower incidence of recurrent bleeding with urgent DBE (within 72 hours after the last visible GI bleeding) compared with non-urgent DBE (diagnostic yield of 70% vs 30%; P < .05) in 120 patients with obscure smallbowel bleeding. These studies suggest that early intervention with DBE may yield better outcomes.…”
Section: Role Of Vcementioning
confidence: 97%
“…However, a small recent study actually suggests that emergency DBE is technically feasible and may facilitate the diagnosis and management of patients with massive overt small bowel hemorrhage ( 90 ). A more recent study also suggests that urgent DBE is better than non-urgent DBE and is associated with a lower recurrent bleeding rate ( 91 ). In addition, one study suggests that repeat DBE from the same direction may also be benefi cial, particularly if the patient had a prior positive DBE ( 92 ).…”
Section: Endoscopic Visualization Of the Small Intestinementioning
confidence: 99%
“…The lesion-specific diagnostic yield for emergency CE reported by different authors ranged between 60 and 73.3%, with only fresh blood without identifiable lesions detected in 6.7–27% of cases. 2 , 11 , 12 Vascular lesions are the most common finding but ulcers and tumours ( Fig. 2 ) have also been reported.…”
Section: Emergency Capsule Endoscopymentioning
confidence: 99%
“…Emergency DAE has been defined by different authors as performance within 24–72 h of clinical presentation. 3 , 11 Severe OOGIB has been widely described as that occurring with haemodynamic instability and transfusion requirements.…”
Section: Conceptsmentioning
confidence: 99%